High insecticide resistance in the major malaria vector Anopheles coluzzii in Chad Republic - Sulaiman S. Ibrahim; Amen N. Fadel; Magellan Tchouakui; Ebai Terence; Murielle J. Wondji; Micareme Tchoupo; Clement Kérah-Hinzoumbé; Samuel Wanji; Charles S. Wondji (BMC, 2019)
Abstract Background The Sahel region of Chad Republic is a prime candidate for malaria pre-elimination. To facilitate pre-elimination efforts in this region, two populations of Anopheles coluzzii from Central Chad Republic were characterized, their insecticide resistance profile and the possible molecular mechanisms driving the resistance in the field investigated. Methods Bloodfed female Anopheles gambiae s.l. resting indoor, were collected at N'djamena and Massakory, Chad in 2018 and characterized for species composition, and infection rate was determined using the TaqMan assay. Susceptibility to various insecticides was assessed using WHO tube bioassays. Cone bioassays were conducted using various long-lasting insecticidal nets (LLINs). Results were analysed using Chi Square test. Knockdown resistance (kdr) and ace-1 markers were investigated by TaqMan genotyping. Results Anopheles coluzzii was the major vector found in N'djamena (100%) and Massakory (~ 94%). No Plasmodium was found in 147 bloodfed F0 An. coluzzii (82 from N'djamena and 65 from Massakory). High intensity pyrethroid resistance was observed with mortalities of < 2% for permethrin, deltamethrin and etofenprox, and with < 50% and < 60% dead following exposure to 10× diagnostic doses of deltamethrin and permethrin, respectively. For both sites, < 10% mortalities were observed with DDT. Synergist bioassays with piperonylbutoxide significantly recovered pyrethroid susceptibility in Massakory populations, implicating CYP450s (mortality = 13.6% for permethrin, χ 2 = 22.8, df = 1, P = 0.0006; mortality = 13.0% for deltamethrin, χ 2 = 8.8, df = 1, P < 0.00031). Cone-bioassays established complete loss of efficacy of the pyrethroid-based LLINs; and a 100% recovery of susceptibility following exposure to the roof of PermaNet®3.0, containing piperonylbutoxide. Both populations were susceptible to malathion, but high bendiocarb resistance was observed in Massakory population. The absence of ace-1 mutation points to the role of metabolic resistance in the bendiocarb resistance. Both 1014F and 1014S mutations were found in both populations at around 60% and < 20% respectively. Sequencing of intron-1 of the voltage-gated sodium channel revealed a low genetic diversity suggesting reduced polymorphism. Conclusions Multiple resistance in An. coluzzii populations from Chad highlight challenges associated with deployment of LLINs and indoor residual spraying (IRS) in the Sahel of this country. The pyrethroid-synergists LLINs (e.g. PermaNet®3.0) and organophosphate-based IRS maybe the alternatives for malaria control in this region.